2014
DOI: 10.3109/03630269.2014.927363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients from Nigeria and the USA Highlights Modifiable Risk Factors for Sickle Cell Anemia Complications

Abstract: To identify factors that affect manifestations of sickle cell anemia we compared patients 11-30 years of age from University of Ibadan, Nigeria (n = 214) and University of Illinois at Chicago, USA (n = 209). Paralleling findings in the general populations of the two countries, the Chicago patients were more often overweight or obese as defined by the Centers for Disease Control (Atlanta, GA, USA) guidelines, and more often had elevated blood pressure (BP) as defined by the National Heart, Lung, and Blood Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The current study confirms this finding, even in a SCA cohort, a similar finding reported in developed countries (Pegelow et al, 1997; Desai et al, 2012) and in Africa (Akingbola et al, 2014). With the improved survival of patients with SCA, the incidence of hypertension is expected to rise, thus screening and awareness are required to prevent the expected complications.…”
Section: Discussionsupporting
confidence: 92%
“…The current study confirms this finding, even in a SCA cohort, a similar finding reported in developed countries (Pegelow et al, 1997; Desai et al, 2012) and in Africa (Akingbola et al, 2014). With the improved survival of patients with SCA, the incidence of hypertension is expected to rise, thus screening and awareness are required to prevent the expected complications.…”
Section: Discussionsupporting
confidence: 92%
“…None of the patients was on hydroxyurea during the duration of this study and this may be due to poor knowledge and perception of physicians towards its use and the issue of cost and its side effects. A recent comparative study among sickle cell patients from Nigeria and the USA showed significant lower use of hydroxyurea among the Nigerian cohort50. Also the locally developed anti-sickling agent, Ciklavit®, which has been found to be effective in reducing sickling episodes, was not prescribed for any of the patients during the study51.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of anemia, a history of recurrent acute chest syndrome, obesity, and elevated blood pressure are all considered independent risk factors for the development of stroke (Akingbola et al, 2014;Ohene-Frempong et al, 1998;Wang et al, 2008). Other risk factors include prior transient ischemic attack, low steady-state hemoglobin levels, hypertension, and high leukocyte counts (Ohene-Frempong et al, 1998).…”
Section: Stroke In Scdmentioning
confidence: 99%